Harvesting resilience - setting the Stage: How can we bridge the disconnects between food security, climatic and natural disaster Early Warning Systems and the anticipatory actions that pastoral and agro-pastoral communities in the Horn of Africa can take? - Lazarus, Brenda (Food and Agriculture Organization of the United Nations, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025